The Use 360 Degree Feedback Method in Evaluate and Improving the GAPS of Competencies: Case Study at PT EIGERINDO MPI - Salman, Salman; Bangun, Yuni Ros (Journal of Business and Management, 2015)
Abstract- The background of this research is due to the doubts of the company director in evaluating competency of his employees. Based on that, the purpose of this research is to find out competency requirements from HR, develop competency evaluation method and identify competency gaps out of the evaluation, and then to provide suggestion and recommendation for PT Eigerindo Multi Produk Industri. PT Eigerindo Multi Produk Industri is the producer and distributor of outdoor gear most known as Eiger. The name Eiger is inspired from a gallant mount of the Alps of Bernese, Switzerland, mount Eiger. Established on 17 of August 1989 and has 125 stores all over Indonesia until now.The methodology used in this research is 360 degree feedback evaluation method. The feedback is done with competency identification. The definitions of competency are mostly taken from Spencerâ€™s competency dictionary, and chosen based on HR section chief interviewed. The data analysis starts from create job key performance indicator, identify requirements of competencies, and determine the expected and current levels of competency. Then followed by calculate the competency gaps using simple substraction of expected level to current level, and find out the gaps which have urgency to be improved, and give recommendation of improvement for PT Eigerindo Multi Produk Industri.From this research, there will be a conclusion and some recommendations. The result shown there are four employee job positions that can be evaluated. Furthermore, there are several significant gaps occur in each of job position while averaging the competency gaps for sales and retail division, which is lead to some incompatibility between existing employees competence with their job requirements. At the end of this research, there will be several recommendations for company and further researcher. The recommendations for the company are to educate and train the evaluated employees and use the calculation of 360 degree evaluation on this study as a reference. Furthermore, another recommendation is addressed for further researcher to create recommendation of improvement by also find out about the closeness of evaluators with the ones evaluated.Keywords: competency, key performance indicator, 360 feedback evaluation, competency gapsÂ